EDUKASI TENTANG TEKNIK RELAKSASI LIMA JARI TERHADAP PENURUNAN TINGKAT KECEMASAN PASIEN PRA OPERASI SECTIO CAESAREA - Septa Dwi Insani; Peny Ariani; Husna Sari (Jurnal Pengabdian Masyarakat Putri Hijau, 2022)
In 2007 the incidence of cesarean section in Indonesia was 921,000 out of 4,039,000 deliveries (22.8%) of all deliveries. The operation to give birth to a child through an incision in the abdominal wall and uterus is called a cesarean section. If a person experiences deep feelings and pressures that cause psychiatric problems which can develop over a long period of time it can cause anxiety that happens to everyone. Anxiety that is not handled seriously will have an impact and impact on the physical and psychological aspects of pregnant women, both for the mother and the fetus. The fear that is usually expressed directly is the anxiety that can be seen in every individual who will undergo surgery. The five finger relaxation technique is one of the nursing interventions that can be done. The problem that occurs is that surgery often causes fear that has an impact on anxiety, resulting in decreased uteroplacental circulation, reduced blood and oxygen flow to the uterus and decreased uterine contractions. An alternative way out of this problem that can be done is to provide education about non-pharmacological therapy, namely five finger therapy. The services provided for pregnant women who will perform a caesarean section in the Hybrid room of the Sembiring Hospital are 19 people. The results showed that the education provided went smoothly and the level of anxiety in pre-cesarean mothers decreased.